Fundamentals of Electrical Drives - Veltman, André; Pulle, Duco W.J.; de Doncker, R.W.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2007)
Electrical drives in general play a key role in power generation, household appliances, automotive and industrial applications. The rapidly expanding area of adjustable speed drives as used in robotics, wind turbines and hybrid vehicles is driven by innovations in machine design, power semi-conductors, digital signal processors and simulation software. This brings us to the purpose of this book namely to help students and engineers appreciate and understand the fundamental concepts of modern electrical drives. An interactive learning approach is taken in this text: theory and calculations are augmented by generic models which are transposed to a simulation platform. The 'build and play' method used in this text visualizes the dynamic operation of a comprehensive set of modules ranging from an inductance to a novel 'ideal rotating transformer' (IRTF). This module is at the center of the generic models used in this text to explore the dynamic and steady state operation of grid and converter fed induction, synchronous and DC machines. The section on modulation and control emphasizes the role of power electronics and digital signal processors in drives. Downloadable files that accompany this text have an extensive set of 'build and play' tutorials, in Simulink R° and Caspoc. The latter is a simulation platform which allows direct access to the 'build and play' modules, without further licensing needs. All figures in this text are included in the downloadable files in order to help with the preparation of customized Power Point type lecture material. Fundamentals of Electrical Drives is for readers with a basic engineering knowledge who have a need or desire to comprehend and apply the theory and simulation methods which are applied by drive specialist throughout the world.
SIMPLE ELECTRO-MAGNETIC CIRCUITS -- THE TRANSFORMER -- THREE-PHASE CIRCUITS -- CONCEPT OF REAL AND REACTIVE POWER -- SPACE VECTOR BASED TRANSFORMER MODELS -- TO ELECTRICAL MACHINES -- VOLTAGE SOURCE CONNECTED SYNCHRONOUS MACHINES -- VOLTAGE SOURCE CONNECTED ASYNCHRONOUS (INDUCTION) MACHINES -- DIRECT CURRENT MACHINES -- ANALYSIS OF A SIMPLE DRIVE SYSTEM.
Keywords: Energy systems; Power electronics; Control engineering; Robotics; Mechatronics; Machinery; Computer simulation; Energy; Energy Systems; Power Electronics, Electrical Machines and Networks; Control, Robotics, Mechatronics; Machinery and Machine Elements; Simulation and Modeling; Energy, general